STATEMENT OF COMPREHENSIVE INCOME ANALYSIS AFTER THE IMPLEMENTATION OF IFRS IN BRAZIL - Silva, Adolfo Henrique Coutinho e; Silva, Érica Gomes Rocha da (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
This study examined the information content of the Comprehensive Income Statement published by 62 companies of “New Market” of BM & FBovespa. The statistical analysis consisted of the application of the mean difference paired test (T test and Wilcoxon test). In addition, a qualitative analysis was performed. The results indicated that: (a) approximately 50% of companies reported gains and losses in Comprehensive Income Statement; (b) the effects of gains and losses were positive in 2012 and 2011 and negative in 2010; (c) the CPC 2 (Effects of changes in exchange rates and translation of financial statements) and CPC 38 (Financial Instruments) were the most frequent; and d) there are differences between metrics Net Income and Comprehensive Income for the companies analyzed in years 2011 and 2010. The results indicate that the items of the DRA have the potential to generate volatility in the income statement if they were recognized in the Income Statement.